Diagnostic Yield of Pleuroscopy in Undiagnosed Pleural Effusions - Abbas, Izza; Satti, Shahzeb Ahmed; Imran, Muhammad; Hussain, Maryam; Ali, Karamat; Raza, Hassan (Pakistan Armed Forces Medical Journal, 2025)
Objective: To evaluate the diagnostic yield of pleuroscopy in undiagnosed pleural effusions. Study Design: Cross-sectional study Place and Duration of Study: Pulmonology Department of Pakistan Emirates Military Hospital (PEMH), Rawalpindi, Pakistan, from Mar to Aug 2023. Methodology: This study selected ninety-eight patients having undiagnosed pleural effusions, aged 15-70 years. Both genders with symptoms of weight loss, fever, cough, and smoking were included through non-probability consecutive sampling. Informed consent was taken before enrolling patients, moderate sedation was given to the patients before the procedure. Complications were recorded. Results: A total of 98 patients with mean age of 56.6±7.6 years, 24(24.49%) were female, and 74(75.51%) male patients were included. 64(64.3%) patients had malignancy, 22(22.5%) had benign pleural effusions and findings of 13(12.2%) had remained undiagnosed or inconclusive. The diagnostic yield after pleuroscopy was reported to be 87.7%. Post-Pleuroscopy complications comprised an overall rate of 9.2%, were identified. Conclusion: The study demonstrates that Pleuroscopy offers a high diagnostic yield in evaluating undiagnosed pleural effusions, confirming its effectiveness and safety. The findings of the study confirm that Pleuroscopy should be considered a valuable tool in the diagnostic and therapeutic management of exudative pleural effusions. Its precision and patient satisfaction support its wider use in clinical practice.